Inovasi Pembelajaran Bahasa Arab Dengan Metode Berlitz Dalam Meningkatkan Keterampilan Berbicara Bahasa Arab Pada Siswa Kelas X di Asrama Bilingual SMA Takhassus Al-Qur’an Wonosobo - Nahriya Ikrima Kholiliya; Asep Sunarko; Vava Imam Agus Faisal (DAS Institute, 2024)
This study aims to determine the effectiveness of the Berlitz method in improving the speaking skills of grade 10 students at the Bilingual Boarding School of the Specialized Al-Qur'an SMA Kalibeber Wonosobo. Arabic speaking skills involve the ability of students to speak and express themselves orally in Arabic. This study uses a quantitative approach with an experimental method using a pretest-posttest control design. The research subjects were 21 grade 10 students of the Bilingual Boarding School of the Specialized Al-Qur'an SMA Kalibeber Wonosobo as the experimental class and 20 grade 11 students of the Bilingual Boarding School of the Specialized Al-Qur'an SMA Kalibeber Wonosobo as the control class. Learning in the experimental class used the Berlitz method, while learning in the control class did not use the Berlitz method. After the learning process was completed, a final test in the form of oral questions was carried out. Then the test results were analyzed and compared using the gain test and t-test to determine the improvement and difference in Arabic speaking skills between the two classes. Furthermore, data sources were obtained using documentation and tests. The results of the study indicate that: 1) The application of the Berlitz method is proven to be effective in improving students' bilingual speaking skills, 2) There is an increase in the Arabic speaking skills of bilingual students after the application of the Berlitz method 3) There is a difference in Arabic speaking skills of students with the application of the Berlitz method with the results of data analysis calculations obtained that the results of the study using the t-test and gain test show that there are 2 objectives that there are differences and improvements in Arabic speaking skills, the results of the gain test for the experimental class are 0.727 and the control class is 0.531. While the results of the hypothesis test obtained tcount = 10.210 and ttable = 2.707 for α = 5% and 2.022 for α = 1% with (df) = (n1-1) + (n2-1) = (21-1) + (20-1) = 39 it can be concluded that the Arabic speaking skills of students using the Berlitz method are better than students who do not use the Berlitz method. And there is an increase in the Arabic speaking skills of students who use the Berlitz method.